Vídeo educativo para pessoa idosa submetida ao cateterismo cardíaco - Nepomuceno, Adriana Meira Tiburtino (2024)
The coronary artery disease is the leading cause of mortality worldwide. This disease impacts the quality of life of older adults and places a burden on health services. Diagnosis is performed through cardiac catheterization (CATE), an invasive procedure that carries risks and can cause anxiety in patients. In this context, the hemodynamic nurse plays an important role, offering educational and emotional support to patients before, during, and after the CATE procedure. The objectives of this research were: 1) to map the evidence in the literature on the effects of educational technologies for elderly people undergoing CATE; 2) to identify the main feelings of these patients regarding the CATE procedure; and 3) to create an educational video on proper preparation, the procedure itself, and post-exam care. The study employed a methodological approach that included a scoping review, qualitative research with older adults undergoing the procedure, and the creation of an educational video. The first stage comprised 20 studies, mostly published in 2021, from Iran, conducted by nurses, with randomized experimental design. The technologies used were predominantly educational videos, which impacted psychological and physiological aspects, knowledge level, and quality of care. The qualitative research was descriptive and exploratory, based on semi-structured interviews with older adults with undiagnosed heart conditions who underwent cardiac catheterization at the Hemodynamics Unit of Lauro Wanderley University Hospital. The non-probabilistic convenience sample included 25 participants. Data were qualitatively analyzed using the Iramuteq software. The multivariate textual analysis through Descending Hierarchical Classification identified four main classes: Positive perceptions about cardiac catheterization; Importance of health education; CATE guidelines; and Perceptions about catheterization. The results showed that many patients experience feelings of fear, anxiety, and uncertainty. However, patient expectations toward the educational process were positive after receiving guidance and information, as they reported greater understanding and confidence regarding the procedure. Finally, an educational video was developed consisting of 49 screens, with image and sound resources, standing out as an important educational tool that provides clearer information for these individuals and reduces the possibility of complications during or after the procedure. It is an interactive educational technological resource with accessible language that offers clear, objective, and dynamic information on the subject.